Successful treatment of severe leptospirosis with steroids and antibiotics: A case report highlighting clinical course and management strategies (Indian Journal of Case Reports, 2024)
Leptospira is the most common zoonotic disease which is now being reported further by physicians due to increased awareness and better testing facilities. Its clinical presentation is varied and most cases resolve spontaneously or even after being mislabeled and treated as viral fever. Those that complicate can cause multiple organ dysfunction syndrome and even fatality. We present the case of a 37-year-old lady with multi-organ dysfunction due to severe icteric leptospirosis and her successful management at our center with antibiotics and steroids. Leptospirosis with its varied presentations is often missed by clinicians not keenly searching for the disease. An ardent eye is a must to clinch the diagnosis and treat early with widely available and effective antibiotics.